2022
DOI: 10.1002/eqe.3764
|View full text |Cite
|
Sign up to set email alerts
|

Development and investigation of an innovative shape memory alloy cable‐controlled self‐centering viscoelastic coupling beam damper for seismic mitigation in coupled shear wall structures

Abstract: To improve the seismic performance of coupled shear walls in high‐rise buildings and to eliminate the problems of large residual deformation and relatively small initial stiffness and damping properties of the traditional viscoelastic coupling beam damper (TVCBD), an innovative shape memory alloy (SMA)‐cable‐controlled self‐centering viscoelastic coupling beam damper (SVCBD) with energy dissipation and self‐centering capabilities was designed and investigated in this study. The construction form and operating … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 73 publications
0
5
0
Order By: Relevance
“…The superelastic mechanical properties of austenitic SMA are not only related to the material's chemical composition, preparation, and heat treatment process but also to the working environment temperature, strain amplitude, number of cycles, loading rate, and stress mode. Previous studies have shown that [9,39,[43][44][45]: the superelastic behavior of unused austenitic SMA will undergo large performance degradation, which is mainly manifested by the decrease of phase transformation stress, the accumulation of residual strain, and the attenuation of energy dissipation capacity. Hence, achieving stable superelastic mechanical properties through mechanical training (e.g.…”
Section: Effect Of Pre-training On Mechanical Properties Of Sma Cablementioning
confidence: 99%
“…The superelastic mechanical properties of austenitic SMA are not only related to the material's chemical composition, preparation, and heat treatment process but also to the working environment temperature, strain amplitude, number of cycles, loading rate, and stress mode. Previous studies have shown that [9,39,[43][44][45]: the superelastic behavior of unused austenitic SMA will undergo large performance degradation, which is mainly manifested by the decrease of phase transformation stress, the accumulation of residual strain, and the attenuation of energy dissipation capacity. Hence, achieving stable superelastic mechanical properties through mechanical training (e.g.…”
Section: Effect Of Pre-training On Mechanical Properties Of Sma Cablementioning
confidence: 99%
“…[1][2][3] As a very effective passive damping control device, VEDs had the advantages of simple construction, easy fabrication, and low cost, so they had splendid application prospects in practical engineering. [4][5][6] Scholars conducted a very large number of studies on VEDs and achieved many valuable research results, which made outstanding contributions to the high-quality application and development of viscoelastic vibration damping technology. Christopoulos and Montgomery investigated the effects of frequency and strain on the mechanical performance of VEDs by testing the mechanical properties of five VEDs.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, viscoelastic dampers (VEDs), which can provide stiffness and damping, have been introduced into the field of civil engineering structural vibration control for seismic enhancement of structures 1–3 . As a very effective passive damping control device, VEDs had the advantages of simple construction, easy fabrication, and low cost, so they had splendid application prospects in practical engineering 4–6 . Scholars conducted a very large number of studies on VEDs and achieved many valuable research results, which made outstanding contributions to the high‐quality application and development of viscoelastic vibration damping technology.…”
Section: Introductionmentioning
confidence: 99%
“…The superelasticity of SMA will form hysteresis loops during cyclic loading, which can dissipate energy and is a good material for vibration control. [19][20][21] At present, SMA has achieved good applications in seismic mitigation of civil structures, including isolation devices, energy dissipation devices and displacement control devices. [22][23][24][25][26][27] An SMA ring spring is composed of an SMA ring and two steel rings (Figure 1).…”
Section: Introductionmentioning
confidence: 99%
“…Superelasticity is the property in that SMA is loaded at a higher temperature to cause a large deformation and can return to the initial shape when the external force is released. The superelasticity of SMA will form hysteresis loops during cyclic loading, which can dissipate energy and is a good material for vibration control 19–21 . At present, SMA has achieved good applications in seismic mitigation of civil structures, including isolation devices, energy dissipation devices and displacement control devices 22–27 …”
Section: Introductionmentioning
confidence: 99%